DEVELOPMENT OF AN ANDROID-BASED KOBOTOOLBOX ASSESSMENT APPLICATION FOR THE IDENTIFICATION OF SPECIFIC LEARNING DIFFICULTIES IN ELEMENTARY SCHOOLS - Dewi Jayanti; Abdullah Pandang; Parwoto Parwoto (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to develop an assessment application based on KoboToolbox to identify specific learning difficulties in elementary school students. The main objectives are to determine user needs, design a prototype, and evaluate the application's validity and practicality. The research employs a mixed-methods approach combined with Research and Development (R&D) using the Borg and Gall model. Findings indicate that teachers urgently need a practical digital assessment tool. The application was successfully developed with a user-friendly Android-based interface. Expert validation results showed a validity level of 92% (categorized as very valid), while the practicality test reached 89% (categorized as very practical). The application is considered effective as a support tool for early and structured detection of specific learning difficulties in elementary school settings.